Cultural Identity in International Relations: Analysis of the Concept of Polewali Mandar International Folk and Art Festival (PIFAF) in West Sulawesi Through Three Principles of Cultural Diplomacy - Rezqi Ahmad Muhammad Putra; Sidik Jatmika (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
This journal aims to analyze the role of national identities in international relations through research on the Polewali Mandar International Folk & Art Festival (PIFAF), which is held in Barat Island. The current study makes use of a qualitative methodology and focuses on three principles of diplomacy in the realm of business, namely, mutual understanding dialogue, culture of exchange, and cross-border collaboration. This study clarifies how PIFAF functions as a crucial platform for enhancing regional identity and tying it in with international connections. This festival creates a space for the discussion of religious ideas, helps to reduce negative bias, and promotes religious understanding among international participants by showcasing festival essentials such as local cuisine, music, dance, and traditional rituals to foreign visitors. Such a plan creates new opportunities for positive public diplomacy. The four-point collaboration principle is explained in the PIFAF context. Through collaboration, this festival gives local educators and senior citizens a chance to interact with international partners and foster knowledge and creativity that can increase worldwide awareness of global development issues. All of the analysis indicates that PIFAF plays a significant role in developing strong local identities and, occasionally, creating new standards for international joint work. The principles of diplomacy in religion that are presented at this festival provide a starting point for understanding religious texts that are more widely accepted among many religious groups, have the potential to strengthen international relations, and encourage more intense global cooperation.